2009
DOI: 10.1182/blood-2008-08-173195
|View full text |Cite
|
Sign up to set email alerts
|

A protease-resistant immunotoxin against CD22 with greatly increased activity against CLL and diminished animal toxicity

Abstract: Immunotoxins based on Pseudomonas exotoxin A (PE) are promising anticancer agents that combine a variable fragment (Fv) from an antibody to a tumor-associated antigen with a 38-kDa fragment of PE (PE38). The intoxication pathway of PE immunotoxins involves receptor-mediated internalization and trafficking through endosomes/lysosomes, during which the immunotoxin undergoes important proteolytic processing steps but must otherwise remain intact for eventual transport to the cytosol. We have investigated the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
191
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(198 citation statements)
references
References 44 publications
(53 reference statements)
5
191
1
1
Order By: Relevance
“…The direct genetic modification used in this study eliminates the additional step of PEGylation and retains the full cytotoxic capability of parental molecule. Other studies have shown that using genetic engineering to mutate T-cell-specific epitopes and the proteolytic cleavage site can improve the pharmacokinetic profile and in vivo efficacy of the biological drug (Tangri et al, 2005;Weldon et al, 2008). Additional studies may show that incorporation of similar mutations into EGF4KDEL 7Mut can further enhance its already potent antitumour activity.…”
Section: Discussionmentioning
confidence: 99%
“…The direct genetic modification used in this study eliminates the additional step of PEGylation and retains the full cytotoxic capability of parental molecule. Other studies have shown that using genetic engineering to mutate T-cell-specific epitopes and the proteolytic cleavage site can improve the pharmacokinetic profile and in vivo efficacy of the biological drug (Tangri et al, 2005;Weldon et al, 2008). Additional studies may show that incorporation of similar mutations into EGF4KDEL 7Mut can further enhance its already potent antitumour activity.…”
Section: Discussionmentioning
confidence: 99%
“…HA22-LR (molecular weight 50.5 kDa) is smaller than HA22 (molecular weight 63 kDa) and consequently has a shorter half-life in mice (15 vs. 8 min) (17). To assess the half-life of HA22-LR-LO10, BALB/c mice were injected with 10 μg of either HA22-LR or HA22-LR-LO10 and bled at intervals between 2 and 60 min.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the half-life of HA22-LR-LO10, BALB/c mice were injected with 10 μg of either HA22-LR or HA22-LR-LO10 and bled at intervals between 2 and 60 min. We measured the concentration of RIT in mice sera by ELISA (14,17). Data were fit to a single exponential decay function.…”
Section: Resultsmentioning
confidence: 99%
“…Bm-svv was then expressed in non-permissive or permissive cells to determine its effect on cell activity using the Cell Counting Kit-8 (CCK-8), which has been frequently employed in mammalian cells (Weldon et al 2009;Ding et al 2010;Kunz et al 2009;Tamura et al 2010), and found that this method is also useful for the determination of insect cell activity.…”
Section: Introductionmentioning
confidence: 99%